DIFFERENTIAL PATHOMORPHOLOGICAL ASSESSMENT OF ACUTE AND CHRONIC RENAL INJURY IN MYOCARDIAL INFARCTION - Shakirov Sardor Abdusaminovich (International Journal of Literature and Language Studies, 2026)
The article focuses on differential pathomorphological assessment of acute and chronic renal injury in patients who died during the acute phase of myocardial infarction. Based on 191 autopsy cases, morphological criteria are specified for distinguishing acute ischemic tubular injury from background nephrosclerosis and their combined form. The decisive diagnostic value belongs not to isolated sclerosis, dystrophy or vascular hyalinosis, but to the correlation of temporal, topographic and cellular signs. A practical diagnostic scheme for autopsy reporting is proposed.